Effect of Microstructure Morphology of Q&P Steel on Carbon and Manganese Partitioning and Stability of Retained Austenite - Huan Xiao; Gang Zhao; Deming Xu; Yuanyao Cheng; Siqian Bao (Metals, 2022)
In this study, we used 0.2C-1.7Si-1.9Mn wt% cold-rolled sheet as the experimental material to prepare the Q&P sample with blocky microstructures and the QQ&P sample with lath-shaped microstructures through the Q&P and QQ&P processes, respectively. The partitioning behavior of carbon and manganese in the two samples after intercritical annealing and partitioning were studied. During the intercritical annealing, the partitioning of carbon and manganese in the Q&P and the QQ&P samples occurred, resulting in the contents of carbon and manganese being significantly higher than those in the ferrite. Meanwhile, due to the migration of the ferrite–austenite interface during the formation of the austenite, the distributions of carbon and manganese in the lath-shaped and blocky austenite were both homogenous. The morphology of the microstructures had little influence on the distribution of carbon and manganese in metastable austenite during intercritical annealing. In the partitioning, the migration of the ferrite–austenite interface and diffusion of manganese can be ignored. Carbon first diffuses from the ferrite grains to the ferrite–austenite interface and then diffuses in the austenite grains. The morphology of the microstructures has a great effect on the homogenization of carbon in austenite grains. Compared with coarse blocky austenite, lath-shaped austenite can shorten the diffusion path of carbon in austenite grains and increase the homogeneity of carbon in austenite grains, thereby improving the thermal stability of lath-shaped austenite. Compared with the Q&P sample, the QQ&P sample has higher content of retained austenite (14.74% vs. 13.96%), better elongation (25.9% vs. 19.2%), and higher product of strength and elongation (27.5 GPa% vs. 24.4 GPa%).